2002
DOI: 10.1128/jvi.76.5.2062-2074.2002
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Cleavage of Ribosome-Associated Poly(A)-Binding Protein by Enterovirus 3C Protease

Abstract: Poliovirus (PV) causes a rapid and drastic inhibition of host cell cap-dependent protein synthesis during infection while preferentially allowing cap-independent translation of its own genomic RNA via an internal ribosome entry site element. Inhibition of cap-dependent translation is partly mediated by cleavage of an essential translation initiation factor, eIF4GI, during PV infection. In addition to cleavage of eIF4GI, cleavage of eIF4GII and poly(A)-binding protein (PABP) has been recently proposed to contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
136
2
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(151 citation statements)
references
References 75 publications
(82 reference statements)
12
136
2
1
Order By: Relevance
“…1C), whereas potent hydrolysis was found using this antibody in cells trans-fected with pTM1-3C, pTM1-2A, or pTM1-HIV-1PR (24). In this regard, PV 2A pro exhibited low proteolytic activity against PABP (25,10). Two lower polypeptides were found in control as well as in 2A…”
Section: Transfection Of Hela Cells With Mrnasmentioning
confidence: 96%
See 2 more Smart Citations
“…1C), whereas potent hydrolysis was found using this antibody in cells trans-fected with pTM1-3C, pTM1-2A, or pTM1-HIV-1PR (24). In this regard, PV 2A pro exhibited low proteolytic activity against PABP (25,10). Two lower polypeptides were found in control as well as in 2A…”
Section: Transfection Of Hela Cells With Mrnasmentioning
confidence: 96%
“…Cleavage of both eIF4GI and eIF4GII strongly blocked the initiation of de novo synthesized mRNAs (17). In addition, PV and Coxsackievirus 2A pro and 3C pro are able to cleave PABP during infection (10). More recently, it has been reported that hydrolysis of PABP by 3C pro in the absence of eIF4G degradation blocks the translation of endogenous mRNAs in HeLa cell extracts (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In animal cells, PABP is cleaved by proteinases of picornaviruses (Joachims et al, 1999;Kerekatte et al, 1999;Kuyumcu-Martinez et al, 2002, 2004bRodriguez Pulido et al, 2007;Zhang et al, 2007), caliciviruses (Kuyumcu-Martinez et al, 2004a) and retroviruses (Alvarez et al, 2006). The resultant cleavage leads to host translational shutdown (Joachims et al, 1999; KuyumcuMartinez et al, 2004a, b;Zhang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro cleavage assays using purified recombinant viral proteases were performed as previously described (31). Briefly, 100 ng of 2A pro or 3C pro or 300 ng of 3CD pro was incubated with 100 g of HeLa cell S10 extract in cleavage buffer (100 mM NaCl, 5 mM MgCl 2 , 10 mM HEPES-KOH, pH 7.4) for 30 min at 37°C.…”
mentioning
confidence: 99%